(untitled) (Educação e Pesquisa, 1999)
This text analyzes the ordering of time in primary state schools of the State of São Paulo at the end of the 19th century and beginning of the 20th century, a period in which the school time architecture is instated and consolidated. The paper thus starts with the first detailed instructions related to time at schools, which are part of the Republican Reform of Public Schooling of 1892. It continues with the regulations elaborated during the First Republic, and progresses up to the creation of the São Paulo State Education Code of 1933, when a new era of state public education begins. This work tries to show that time is an ordering that is experimented and learnt at school. The study is based on documentary sources, especially legislation and official texts from Education Authorities. The analyses focus on two aspects: the political formulation of school time, and the pedagogical and disciplinary organization of time at school. With regard to the first aspect, the work shows how the ordering of time was driven by an aspiration of standardization and control. In that sense, state school authorities attempted to regulate on mandatory schooling, attendance rules, duration of primary education, and daily attendance time. As to the pedagogical and disciplinary aspect, this study stresses the meticulous ordering of school time including the curriculum rationalization - the selection and distribution of knowledge along grades, classes, and lessons, and the definition of timetables.